A profile of a retrospective cohort of 22 patients with COVID-19 and active/treated tuberculosis. Issue 5 (19th November 2020) - Gupta, Nitesh; Ish, Pranav; Gupta, Amitesh; Malhotra, Nipun; Caminero, Jose Antonio; Singla, Rupak; Kumar, Rohit; Yadav, Siddharth Raj; Dev, Nishanth; Agrawal, Sumita; Kohli, Santvana; Sen, M.K.; et al.
We read with interest the two articles by Tadolini et al. [1] and Stochino et al. [2], which described recent cohorts of either current or former tuberculosis (TB) patients with coronavirus disease 2019 (COVID-19) and studied their clinical course. India has the majority of global burden of TB, along with highest rising number of daily COVID-19 cases in the world [3, 4]. The information about COVID-19 and active/former TB co-infection reported so far is sparse, but it can be assumed that person with TB, when co-infected with COVID-19, may be at more risk of poor outcomes [1, 5]. The present study describes the first-ever cohort of current or treated TB patients co-infected with COVID-19 from a high TB burden country, recruited by a tertiary care hospital in India. Both tuberculosis and COVID-19 being communicable and prevalent diseases in India, the co-existence can lead to worse outcomes, as seen in this study, where there was high mortality among active as well as treated TB patients with COVID-19 co-infection https://bit.ly/3jHcGbQ